1998
DOI: 10.1097/00006534-199804050-00001
|View full text |Cite
|
Sign up to set email alerts
|

Static-Electric Field Induction by a Silicone Cushion for the Treatment of Hypertrophic and Keloid Scars

Abstract: Silicone gel and silicone occlusive sheeting are widely used at present for the treatment of hypertrophic and keloid scars, without any scientific explanation as to their mode of action. In a recent paper the possibility was raised that static electricity generated by friction-activated silicone sheeting could be the reason for this effect, and that it can, with time, cause involution of hypertrophic and keloid scars. The objective of this study was to test this hypothesis and to observe whether a continuous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 15 publications
1
39
0
2
Order By: Relevance
“…This static electricity is thought to aid the alignment of collagen cells, thus resulting in the involution of raised scars. 25,27,28 The findings surrounding therapeutic mechanisms support the hypothesis that there are multiple combined processes by which SGS create homeostasis of the skin's barrier function beyond straightforward hydration and occlusion of the scar site. Many suggested factors are regarded as having a significant influence in the overall efficacy of SGS, although some lack thorough clinical support.…”
Section: Mechanisms Of Action Of Sgsmentioning
confidence: 80%
“…This static electricity is thought to aid the alignment of collagen cells, thus resulting in the involution of raised scars. 25,27,28 The findings surrounding therapeutic mechanisms support the hypothesis that there are multiple combined processes by which SGS create homeostasis of the skin's barrier function beyond straightforward hydration and occlusion of the scar site. Many suggested factors are regarded as having a significant influence in the overall efficacy of SGS, although some lack thorough clinical support.…”
Section: Mechanisms Of Action Of Sgsmentioning
confidence: 80%
“…16,19,20 The generation of a charge difference at the skin surface (ie, static electricity) has also been proposed as a possible mechanism by which silicone sheeting affects scar resolution. 21 However, the most prevalent theory has focused on the ability of silicone occlusive dressings to increase hydration of the stratum corneum. 22 It has been suggested that silicone ointment may also be effective, 23 as well as occlusive oil without any silicone product.…”
mentioning
confidence: 99%
“…Various mechanisms have been proposed as possible modes of action for silicone-based agents and corticosteroids in the wound healing processes including: 1) an increased temperature or oxygen tension increasing collagenase activity and leading to collagen breakdown shrinking the scars [3,7], 2) occlusion and hydration of wounds [7,13]; reduction in transepidermal water loss decreases stimulation of keratinocytes which stops cytokine production [13], and 3) polarization of the scar tissue caused by a negative static charge between silicone and skin [14] and the modulation of growth factors [9,15,16].…”
Section: Discussionmentioning
confidence: 99%